Flexible Load of Existing Biogas Plants: A Viable Option to Reduce Environmental Externalities and to Provide Demand-driven Electricity? - David Schaf̈er; Wolfgang Britz; Till Kuhn (German Journal of Agricultural Economics (GJAE), 2017)
The expansion of fluctuating renewable energies such as wind and solar increases the need for electricity produced on demand to stabilize the grid. Electricity from existing biogas plants in Germany allows flexible energy output and is increasingly marketed on demand requiring technical modifications such as increased gas storage and engine capacity. In this study we investigate an
Keywords: 330